PENGARUH KELENGKAPAN PRODUK, KUALITAS PELAYANAN DAN ACCESSIBILITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. LUBRIKAN JASA TAMA - Shantia, Angel; Heryenzus, Heryenzus (LPPM Universitas Putera Batam, 2021)
This study aims to determine the effect of product completeness, service quality and accessibility on consumerpurchasingf decisions at PT. Lubrikan Jasa Tama partially or simultaneously. The data used are primary datacollected through questionnaires to 105 respondents who are consumers of PT. Lubrikan Jasa Tama. Thequestionnaire method uses a Likert scale with probability sampling technique methods. The datas obtained wereanalyzed using descriptive analysis and multiple linear regression analysis. From the results of this study, it canbe seen that the variables of product completeness, service quality and accessibility have an effect on purchasingdecisions, this is indicated by the value of Adjusted R Square of 0.554, which means that product completeness,service quality and accessibility have an effect of 55.4% on purchasing decisions and the rest is equal to 44.6%influencedd by other variables wnot examined. In this study it can also be seen that partially product completenessdoes not affect purchasing decisionss, while service quality and accessibility have a significantt effect onpurchasing decisions. Simultaneously, product completeness, service quality and accessibility have a positiveeand significant effect on purchasing decisions.